Emerging cell cycle related non-coding RNA biomarkers from saliva and blood for oral squamous cell carcinoma - Kalmatte, Asrarunissa; Rekha, Punchappady Devasya; Ratnacaram, Chandrahas Koumar (Molecular biology reports, 2023)
The unnotified or undifferentiable early stages of oral squamous cell carcinoma (OSCC) progression are the prime reasons for late-stage detection and poor survival outcomes of oral cancer. This review summarizes the prior research and recent advancements on the influence of dysregulated non-coding RNA (ncRNA) on cell cycle and their employability as diagnostic and prognostic biomarkers of oral cancer. The literature search was performed using the following keywords: ‘serum/saliva non-coding RNAs’ and ‘serum/saliva non-coding RNAs and cell cycle’, ‘serum/saliva dysregulated ncRNAs and cell cycle’, ‘Cdk/CKI and ncRNAs’, ‘tissue ncRNAs’ concerning ‘oral cancer’’. The compiled data focuses mainly on the diagnostic and prognostic significance of MicroRNAs (miRNAs), Circular RNAs (circRNAs), and Long noncoding RNAs (lncRNAs) on oral cancer and all other cancers as well as subject-relevant articles published in languages other than English are beyond the scope of this review and excluded from the study. Moreover, articles focusing on DNA, protein, and metabolite markers are eliminated from the study. While there exist various potential biomolecules such as DNA, RNA, proteins, metabolites, and specific antigens representing predictive biomarkers in body fluids for oral cancer, this review completely focuses on non-coding RNAs restricted to saliva and blood, picking out a few of the reliable ones amongst the recent investigations based on the sophisticated techniques, cohort, and sensitivity as well as specificity, i.e., salivary miR-1307-5p, miR-3928, hsa_circ_0001874 and ENST00000412740, NR _ 131012 , ENST00000588803, NR _ 038323 , miR-21 in circulation. Thus, further studies are required to clinically confirm the usage of these non-invasive biomarkers in oral cancer.